Tracing The Progression of Smartphone Education: An In-Depth Bibliometric Analysis on The Scopus Database (2013-2023) - Fantofik, Didy; Maksum, Muh. Nur Rochim; Salim, Hakimuddin; Mustofa, Triono Ali; Andhim, Muk.; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The purpose of this research is to examine and evaluate the progression of research on Education Strategies in Scopus-indexed publications. The research method is bibliometric analysis, which investigates publications on Smartphone Education in the Scopus database from 2013 to 2023. The analysis involved tools such as Excel and R/R-Studio. VOSviewer was used to conduct visual analysis, which displayed keyword occurrences and document citations at the same time. This research identified 1216 relevant publications that met the criteria. The results show an annual growth rate of 0%, with a notable peak in 2023. The United States was the main source of publications, with National Taiwan Normal University and Universiti Pendidikan Sultan Idris being the most active institutions. George, B.C was the leading author in the Smartphone Education theme. This research offers a comprehensive overview of the literature in the education field, and suggests areas for future exploration. This research will likely enhance the understanding of educational strategies.